2021
DOI: 10.1021/jacs.1c04624
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Active Site for CO Activation in Fe-Catalyzed Fischer–Tropsch Synthesis from Machine Learning

Abstract: In situ-formed iron carbides (FeC x ) are the key components responsible for Fischer–Tropsch synthesis (FTS, CO + H2 → long-chain hydrocarbons) on Fe-based catalysts in industry. The true active site is, however, highly controversial despite more than a century of study, which is largely due to the combined complexity in both FeC x structures and mechanism of CO hydrogenation. Herein powered by machine learning simulation, millions of structure candidates for FeC x bulk and surfaces are explored under FTS co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 67 publications
1
62
0
Order By: Relevance
“…We note that the phases of indium in the sample were undetectable via XRD. Extensive studies have already shown that Fe 2 C and Fe 7 C 3 are two of the major carbide phases formed during the FTS reaction. Both of them were reported to promote C–C coupling toward olefin and C5+ hydrocarbon formation under the specific reaction conditions, which was kept in line with our study. Details about the effect of carbide phases on catalytic reactivity are not the focus of this study.…”
Section: Results and Discussionsupporting
confidence: 90%
“…We note that the phases of indium in the sample were undetectable via XRD. Extensive studies have already shown that Fe 2 C and Fe 7 C 3 are two of the major carbide phases formed during the FTS reaction. Both of them were reported to promote C–C coupling toward olefin and C5+ hydrocarbon formation under the specific reaction conditions, which was kept in line with our study. Details about the effect of carbide phases on catalytic reactivity are not the focus of this study.…”
Section: Results and Discussionsupporting
confidence: 90%
“…The carbide phase composition depends on the H 2 /CO ratio, iron dispersion, promoters, support, the extent of iron reduction and temperature. 319 Recent machine learning simulation 320 indicated that Fe 5 C 2 , Fe 7 C 3 , and Fe 2 C were the three stable bulk phases under FT synthesis, producing olefins.…”
Section: Light Olefin Synthesis From Carbon Oxidesmentioning
confidence: 99%
“…Recently, data-driven method brought about great success in computer vision 20 , natural language processing 21 and speech recognition 22 . With the inspiration and opportunities of machine learning (ML), amounts of related studies using MLassisted method have emerged for prediction of formation energy of crystals 23 , superhard compounds 24 and catalytic activity [25][26][27][28][29][30][31] . In general, material features should be properly selected for descriptor-to-property mappings in ML.…”
Section: Introductionmentioning
confidence: 99%